Frame erasure concealment method used for wideband embedded speech codec - ZHU Heng; BAO Chang-chun; LI Rui (Tongxin xuebao)
An efficient frame erasure concealment（FEC）method for wideband embedded speech codec was proposed.The erased speech frame was classified as voiced,unvoiced,silence,unvoiced transit to voiced and voiced transit to unvoiced at decoder.The energy of excitations was carefully controlled based on the classification of the speech.To match with the configuration of the embedded speech codec,the adaptive codebook for erased frame was recovered with the last frame’s bit-stream.For increasing the robustness of the codec,the contribution of adaptive codebook was prop-erly constrained at encoder.The proposed FEC method is very simple and has a good performance without extra delay and bits requirements in codec.This method has been applied to an embedded variable bits rate codec submitted to ITU-T as a candidate.